(untitled) (Andamios, Revista de Investigación Social, 2009)
The border towns of northern Mexico have been regarded as spaces little conducive to the culture development. Tijuana is a sign that contradicts the idea, widespread in the past and current today. In recent decades there was a significant boost in different areas of cultural activity in the city, which gradually acquired an outstanding diversity, richness and complexity, traits that currently define their cultural field. This text presents a brief look at the development of Cultural Policy in the city of Tijuana during the twentieth century. It examines the role of social actors involved, the ideological orientation that guided their actions, domains for intervention, as well as the most prominent practices and relationships of these actors in the cultural field of Tijuana.